2020
DOI: 10.1055/s-0040-1708049
|View full text |Cite
|
Sign up to set email alerts
|

Natural Language Processing to Extract Meaningful Information from Patient Experience Feedback

Abstract: Background Due to reimbursement tied in part to patients' perception of their care, hospitals continue to stress obtaining patient feedback and understanding it to plan interventions to improve patients' experience. We demonstrate the use of natural language processing (NLP) to extract meaningful information from patient feedback obtained through Press Ganey surveys. Methods The first step was to standardize textual data programmatically using NLP libraries. This included correcting spelling mistakes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 22 publications
1
44
0
Order By: Relevance
“…Five studies did not perform manual classification and employed existing software to perform the sentiment analysis, that is, TheySayLtd, 28 TextBlob, 52 SentiWordNet, 57 DICTION, 53 Keras. 50 We split the supervised approach based on sentiment analysis ( table 2A ) and text classification ( table 2B ), where we document the percentage of total comments manually classified into categories for sentiment and topics for text classification, the number of raters including the inter-rater agreement and the classifier(s) used for ML. In addition, where reported, we also highlight the configuration employed during the data processing steps.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies did not perform manual classification and employed existing software to perform the sentiment analysis, that is, TheySayLtd, 28 TextBlob, 52 SentiWordNet, 57 DICTION, 53 Keras. 50 We split the supervised approach based on sentiment analysis ( table 2A ) and text classification ( table 2B ), where we document the percentage of total comments manually classified into categories for sentiment and topics for text classification, the number of raters including the inter-rater agreement and the classifier(s) used for ML. In addition, where reported, we also highlight the configuration employed during the data processing steps.…”
Section: Resultsmentioning
confidence: 99%
“…This fails to capture the mixed sentiments or neutral sentiments which could provide useful insights into patient experience. Nawab et al 50 demonstrated that splitting the mixed sentiments by sentences revealed distinct sentiments. Therefore, although the percentage of mixed or neutral sentiment is low compared with the overall dataset, analysis of comments within these mixed and neutral sentiment can provide useful information and therefore should not be discarded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] The algorithms systematically split free text into individual segments (words and phrases), correct spelling mistakes, standardize abbreviations, and analyze the syntax and semantics of each individual segment to decide whether a concept or sentiment is present within the free text. 12,13 It is a powerful tool when there is a large set of unstructured data, and it allows us gain unique insights that may be difficult to appreciate otherwise, for example, analyzing patient feedback that is written in natural language. 13 A recent review, 9 examined 67 articles on NLP for radiology, reports that clinical support service was a major category of use.…”
Section: Background and Significancementioning
confidence: 99%
“…12,13 It is a powerful tool when there is a large set of unstructured data, and it allows us gain unique insights that may be difficult to appreciate otherwise, for example, analyzing patient feedback that is written in natural language. 13 A recent review, 9 examined 67 articles on NLP for radiology, reports that clinical support service was a major category of use. NLP has also been used with progress notes to identify disease processes or to aid in billing and coding.…”
Section: Background and Significancementioning
confidence: 99%